2012
DOI: 10.1159/000346446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies on the Treatment of Cancer Cachexia with Megestrol Acetate plus Thalidomide

Abstract: Background: The management of cancer-related anorexia/cachexia syndrome (CACS) is a great challenge in clinical practice. To date, practice guidelines for the prevention and treatment of CACS are lacking. The authors conducted a randomized study to confirm the effectiveness and safety of treatment of CACS utilizing megestrol acetate (MA) plus thalidomide. Methods: One hundred and two candidates with CACS were randomly assigned to two treatment groups (trial group and control group): the trial group received MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 26 publications
1
62
0
2
Order By: Relevance
“…Previous studies have shown beneficial results in humans with cancer cachexia using appetite stimulants such as megestrol acetate (with or without thalidomide, formoterol, and L‐carnitin) to improve skeletal muscle mass and strength . Beginning in 1993, megestrol acetate was approved in the USA and in several European countries for the treatment of the anorexia–cachexia syndrome .…”
Section: Therapeutic Strategies For Cardiac Cachexiamentioning
confidence: 99%
“…Previous studies have shown beneficial results in humans with cancer cachexia using appetite stimulants such as megestrol acetate (with or without thalidomide, formoterol, and L‐carnitin) to improve skeletal muscle mass and strength . Beginning in 1993, megestrol acetate was approved in the USA and in several European countries for the treatment of the anorexia–cachexia syndrome .…”
Section: Therapeutic Strategies For Cardiac Cachexiamentioning
confidence: 99%
“…[102] Megesterol carries an increased risk of thromboembolism, while thalidomide is known to cause birth defects in pregnant patients.…”
Section: 4 Current and Potential Pharmacologic Therapies For Cimwmentioning
confidence: 99%
“…Clinical trials with drugs such as ghrelin, and thalidomide combined with megasterol acetate do not directly target IL-6, but have demonstrated promise by attenuating some cachectic symptoms in cancer patients, such as appetite, weight gain and a feeling of well-being [50-52]. However, these therapies have the potential to indirectly suppress systemic IL-6 levels or muscle IL-6 production [51, 53]. Recent targeted human therapies for cachexia related to IL-6 have been focused on developing humanized antibodies that could rescue cachexia symptoms.…”
Section: L-6 Targeted Therapeutics: Clinical Studiesmentioning
confidence: 99%